Long Term Evaluation of Biodegradation and Biocompatibility In-Vivo the Mg-0.5Ca-xZr Alloys in Rats - Eusebiu-Viorel Sindilar; Corneliu Munteanu; Sorin Aurelian Pasca; Iuliana Mihai; Madalina Elena Henea; Bogdan Istrate (Crystals, 2021)
Biodegradable alloys in Mg have the advantages of traditional metallic materials and those of biodegradable polymers with superior strength, lower density and ideal rigidity for fixing bone fractures. The biocompatibility and biodegradability of the five concentrations of Mg-0.5Ca-xZr alloys used were assessed using clinical and laboratory examinations that followed over time: tissue reaction, histological and imaging (RX, CT and SEM) evolution at 1, 2, 4 and 8 weeks after implant. The main purpose of this study was to investigate in vivo the long-term effect of Mg-0.5Ca-xZr alloys in rats. The results confirmed that Mg-0.5Ca-xZr alloys are biocompatible and biodegradable and are recommended to be used as possible materials for new orthopedics devices.